Serviço Social e Sistema de Justiça: significado social e processamento do trabalho de assistentes sociais - Souza, Bianca Ribeiro de (2021)
The present thesis has as object the processing of the work of the social worker, and the apprehension of its social meaning in the institutions that form the Justice System of São Paulo State, that is, The Court of Justice, The Prosecution Service and The Public Defender. Therefore, it historicizes the sociopolitical conditions that led to an entry of the social workers within these institutions, it systematizes initial demands and professional answers and restore little known aspects and possible tense situations and conflict that could have trigged; yet, it problematizes attributions and professional competences, based on given demands to the profession and it analizes relations, conditions and the organization of the work of social workers, in a perspective of the totallity. Considering that there are a consolidated debate and a substantial bibliography production about the Social Work in these intitutions, this research was also driven to the analysis of the professional work in a wider way, in other words, beyond each of them, because the presence of an open investigation field is observed when the apprehension of The Social Work is taken into account, based on the inter-relationship of these institutions as Justice System’s components. Following this approach, bibliographical and document researches were done using different sources and field research, grounded in the qualitative methodology, through intentional samples of the Social Worker’s areas of work, where there are intersections of interventions- Childhood and Youth, Childhood and Youth- infraction and Domestic and Family Violence against Women- in the three socio occupational areas of the Justice System of São Paulo city. The field research was done in two phases: in the first one, virtual questionaires were sent to all professionals within these areas, with the intention of mapping the social workers in the Justice System, as well as, the ways of organization of this work, routines and material conditions, techniques and ethics for its achievement. In the second phase, semi structured interviews were conducted with 21 social workers from these three institutions and from the chosen areas, aiming to know and analyze the universe of meanings, through the apprehension of how the work has been processed by the mediation of the attributions and competences. Among the research findings, the analyzes allowed us to conclude that the Social Work in the Justice System is permeated by a double risk: to reproduce, in the profession, the field of dispute in the legal world, and to reinforce interventions that contribute to the fragmented approach of the expressions of the social question within the System